Effectiveness of Project-Based Learning Model on Students' Natural Science Learning Outcomes - Krestina Kusumawati; Tabitha Sri Hartati Wulandari (Bioedukasi: Jurnal Pendidikan Biologi, 2025)
This study aims to determine the effectiveness of the influence of the Project-Based Learning learning model on the learning outcomes of 9th-grade science students at Junior High School 5 Tuban. The type of research used is experimental research, and the research design is a one-group pretest-posttest Design. The population in this study was the ninth-grade students of SMP Negeri 5 Tuban as a whole, while the research sample was class IX-E students, totalling 31 students. The data collection techniques through learning outcome instruments include pretest and post-test scores. The data analysis techniques used are N-Gain Test analysis and descriptive analysis. The results showed that students' average score after applying the PjBL model increased by 29.03; in contrast, the results of the N-Gain analysis showed a value of 0.69 with a sufficient category. This study concludes that the effectiveness of the project-based learning (PjBL) model affects the results of students' natural science learning